The Effect of Podcast as a Medium Towards Students’ Listening Comprehension at English Language and Study Program - Nurzamani, Luqman; Haris, Hannisa; Marleni, Lusi; Sari, Nurhidayah (Universitas Pahlawan Tuanku Tambusai, 2026)
Listening comprehension is a crucial skill in English language learning, yet many university students still face difficulties in understanding spoken texts, particularly in identifying specific information, grasping the main idea, and making inferences. This study aimed to investigate the effect of using podcasts as a learning medium on students’ listening comprehension at the English Language and Education Study Program of the University of Pahlawan Tuanku Tambusai. A quantitative approach with a pre-experimental one-group pretest–posttest design was employed. The participants consisted of 23 first-semester students selected through purposive sampling. The research instrument was a listening comprehension test comprising 30 items measuring three indicators: specific information, gist, and inference. The data were analyzed using descriptive statistics and the Wilcoxon Signed-Rank Test due to non-normal data distribution. The findings revealed a significant improvement in students’ listening comprehension, with the mean score increasing from 47.22 in the pretest to 74.72 in the posttest. The statistical analysis showed a significance value of 0.000 (p 0.05), indicating a significant difference between pretest and posttest scores. These results demonstrate that podcast-based learning has a significant positive effect on improving students’ listening comprehension. Therefore, podcasts can be considered an effective supplementary medium for listening instruction in English language education.